2012
DOI: 10.1111/j.1537-2995.2012.03624.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of point‐of‐care testing for plasma therapy

Abstract: Use of point-of-care testing (POCT) has been driven by limitations of laboratory-based testing as a tool for decisions for transfusions of blood components. Clinical settings such as liver transplantation, cardiothoracic surgery, and trauma are particularly in need of such diagnostic tests because of the complex coagulopathies that can develop in these settings of substantial hemorrhage and need for blood component support. Successful implementation of POCT requires collaboration between surgery, anesthesia, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…66,67 These subjects are particularly in need of coagulation tests because of the complex coagulopathies that can develop from substantial hemorrhage. Effective implementation of the viscoelastic technology, such as thrombelastography or rotational thromboelastometry, had significant effects on the amount of administered freshfrozen plasma, as well as erythrocyte and thrombocyte concentrates in massively transfused patients.…”
Section: Potential Medical Benefitsmentioning
confidence: 99%
“…66,67 These subjects are particularly in need of coagulation tests because of the complex coagulopathies that can develop from substantial hemorrhage. Effective implementation of the viscoelastic technology, such as thrombelastography or rotational thromboelastometry, had significant effects on the amount of administered freshfrozen plasma, as well as erythrocyte and thrombocyte concentrates in massively transfused patients.…”
Section: Potential Medical Benefitsmentioning
confidence: 99%
“…Goodnough & Hill [19] have highlighted the need for POC coagulation testing in clinical settings including liver transplantation, cardiothoracic surgery, and trauma because of the high risk of hemorrhage and the resulting requirements for blood component support. Other research has identified that POC testing in the form of platelet count, PT, aPTT and fibrinogen concentration has resulted in reduced blood loss, shorter surgical times, and reduced transfusion requirements [20,21].…”
Section: The Development Of Point Of Care Coagulation Testingmentioning
confidence: 99%
“…Their main uses are the monitoring of vitamin-K antagonist oral anticoagulants, the assessment of platelet function, in particular in patients undergoing anti-platelets therapy, as well as the rapid evaluation of clotting function in bleeding patients during surgery and in emergency settings [33][34][35][36][37]. Out of these the viscoelastometric POCT devices are particularly useful in giving quick information on all the main phases and components of clot formation, including fibrinogen concentration, platelet activity and fibrinolysis [38].…”
Section: Hemostasismentioning
confidence: 99%